Dr. Anton Korošec, častni občan Bleda - Rozman, Franc (Časopis za zgodovino in narodopisje, 2022)
In this article, the political background of the admission of prominent people to the honorary citizenship of Bled is presented from 1876, when Dr Janez Bleiweiss became the first honorary citizen of Bled, to the time before the Second World War, when Dr Anton Korošec became the honorary citizen of Bled in 1938. Anton Korošec was the recipient of a book of 322 Slovenian municipalities that awarded him the title of Honorary Citizen. This book has been mentioned several times in the literature, but its fate was thought to be unknown.
Keywords: Bled; častni občani; honorary citizens; Korošec, Anton; Slovenian politicians; slovenski politiki